2019
DOI: 10.1002/soej.12374
|View full text |Cite
|
Sign up to set email alerts
|

Appeals to Social Norms and Taxpayer Compliance

Abstract: We use laboratory experiments to examine the impact of appeals to social norms on the compliance decisions of individuals. We test the effects of two main types of social norms: “descriptive norms,” or the type of behavior that is typical or most frequently enacted, and “injunctive norms,” or the type of behavior that “constitutes morally approved and disapproved conduct”. In addition, for injunctive norms, we introduce approval‐framed and disapproval‐framed injunctive norm messages. Our results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…There is also some emerging work on how different forms of communication between the tax authorities and the taxpayers may sometimes increase the social norm of compliance (Onu and Oats, ). Even so, the attempt to increase compliance in controlled field experiments by an appeal to social norms has generally been found to have a mixed impact on compliance, with some controlled field experiments finding no impact (Blumenthal et al ., ; Torgler, ; Fellner et al ., ; Castro and Scartascini, ; Ortega and Scartascini, ; Pomeranz, ) and others finding a positive and significant if small effect (Del Carpio, ; Bott et al ., ; Hallsworth et al ., ; Alm et al ., ). The information that tax authorities have on income sources is an essential component of a compliance strategy . Compliance is far greater on income subject to employer withholding and to third‐party information sources than on income not subject to these features.…”
Section: Insights From Empirical Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…There is also some emerging work on how different forms of communication between the tax authorities and the taxpayers may sometimes increase the social norm of compliance (Onu and Oats, ). Even so, the attempt to increase compliance in controlled field experiments by an appeal to social norms has generally been found to have a mixed impact on compliance, with some controlled field experiments finding no impact (Blumenthal et al ., ; Torgler, ; Fellner et al ., ; Castro and Scartascini, ; Ortega and Scartascini, ; Pomeranz, ) and others finding a positive and significant if small effect (Del Carpio, ; Bott et al ., ; Hallsworth et al ., ; Alm et al ., ). The information that tax authorities have on income sources is an essential component of a compliance strategy . Compliance is far greater on income subject to employer withholding and to third‐party information sources than on income not subject to these features.…”
Section: Insights From Empirical Researchmentioning
confidence: 97%
“…(), Alm et al . (1992a, b, c, , c, d, 2010, , , b, c, d), Alm and McKee (, ), Andrighetto et al . () and Zhang et al .…”
Section: Type Of Income Net Misreporting Percentage (%) Percentage Ofmentioning
confidence: 98%
“…Thus, in using the DTPB, it is possible to combine the influencing factors: ISM usage intention, ISM acceptance, social norms regarding ISM usage, and ISM usage ability into one theoretical model. Nevertheless, previous research has shown that social norms can be looked at from two different perspectivesinjunctive and descriptive normsand have different impacts on behaviors (Alm, Schulze, von Bose, & Yan, 2019). Thus, our theoretical model uses the DTPB and extends the DTPB to include both injunctive and descriptive social norms (see Figure 1).…”
Section: A State Of the Researchmentioning
confidence: 99%
“…While descriptive social norms enjoy relatively more attention from experimenters in the field, Wenzel (2004), Bobek et al (2007) and Alm et al (2019) suggest that injunctive social norms may also potentially incite the desired behaviour, especially if the persons under the treatment can identify themselves with them. However, if the social norms are in conflict with RBF 14,1 the norms already internalised by the person, they can incite opposite reaction and behaviour (Wenzel, 2004).…”
Section: The Behavioural Approach To Increasing Local Tax and Fees Re...mentioning
confidence: 99%